Executable graphics for PBNM - Lopes, Rui Pedro (2005)
The specification of a policy is performed in a policy language, usually following a textual representation. However, humans process images faster than text and they are prepared to process information presented in two or more dimensions: sometimes it is easier to explain things using figures and their graphical relations than writing textual representations. This paper describes a visual language, in the form of graphics that are executed in a networking environment, to define a network management policy. This approach allows to map visual tokens and corresponding arrangements into other languages to which a mapping is defined.